Self-organizing cell tactile perception which depends on mechanical stimulus history. (4th March 2019) - Shimizu, Masahiro; Minzan, Kosuke; Kawashima, Hiroki; Miyasaka, Kota; Umedachi, Takuya; Ogura, Toshihiko; Nakai, Junichi; Ohkura, Masamichi; Hosoda, Koh
Abstract : Living organisms are capable of self-reproduction, self-repair, and high adaptability through self-organization. By applying biological materials such as cells and tissues to a robot, the resulting bio-machine hybrid system can perform important biological functions beyond those of traditional robots. In this study, we focused on the mechanobiological properties of a C2C12 cell, which is an immortalized mouse myoblast cell line. Calcium ion levels increased when the cells were subjected to mechanical stimuli. This type of physiological phenomenon can be applied in novel tactile sensors to develop a bio-machine hybrid system. We verified the tactile sensation characteristics of the cells. We cultured the cells on a thin polydimethylsulfoxane (PDMS) membrane. We applied two types of mechanical stimuli to opposite sides of the PDMS membrane. Next, we observed the cell distributions and quantified the increase in calcium ion levels inside the cells for tactile sensation. Our results demonstrate that the mechanical stimuli caused significant changes in the orientation and local density of cell aggregation. Interestingly, we confirmed that calcium ion increases depend on the history of mechanical stimuli application. GRAPHICAL ABSTRACT: